High Density Lipoprotein and Its Precursor Protein Apolipoprotein A1 as Potential Therapeutics to Prevent Anthracycline Associated Cardiotoxicity - Kluck, George E. G.; Durham, Kristina K.; Yoo, Jeong-Ah; Trigatti, Bernardo L. (Frontiers in Cardiovascular Medicine, 2020)
Cardiovascular disease and cancer are the leading causes of death in developed societies. Despite their effectiveness, many cancer therapies exhibit deleterious cardiovascular side effects such as cardiotoxicity and heart failure. The cardiotoxic effects of anthracyclines such as doxorubicin are the most well-characterized of cardiotoxic anti-cancer therapies. While other anti-neoplastic drugs also induce cardiotoxicity, often leading to heart failure, they are beyond the scope of this review. This review first summarizes the mechanisms of doxorubicin-induced cardiotoxicity. It then reviews emerging preclinical evidence that high density lipoprotein and its precursor protein apolipoprotein A1, which are known for their protective effects against ischemic cardiovascular disease, may also protect against doxorubicin-induced cardiotoxicity both directly and indirectly, when used therapeutically.